2020
DOI: 10.1111/1440-1681.13288
|View full text |Cite
|
Sign up to set email alerts
|

Exendin‐4 exhibits a tumour suppressor effect in SKOVR‐3 and OVACR‐3 ovarian cancer cells lines by the activation of SIRT1 and inhibition of NF‐κB

Abstract: This study investigated if EX‐527 has an anti‐tumour effect in SKOV‐3 and OVCAR‐3 ovarian cancer (OC) cell lines and if this effect involves the SIRT1/NF‐κB axis. Cells were cultured in the presence or absence of EX‐527, a selective SIRT‐1 inhibitor. Exendin‐4 significantly induced cell death in both cell lines and inhibited cell migration and invasion. Also, it decreased protein levels of Bcl‐2, MMP‐9, and ICAM‐1 and increased those of Bax, cyclin D1 and cleaved caspase‐3. Mechanistically, Exendin‐4 increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…MMP-9 is involved in ovarian cancer progression, metastasis, and platinum-drug resistance [ 48 ], and MMP-9 inhibition can improve the standard anticancer treatment efficacy. Acting on the MMP-9 pathway, NF- κ B mediated signaling can be initiated for tumor suppression [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…MMP-9 is involved in ovarian cancer progression, metastasis, and platinum-drug resistance [ 48 ], and MMP-9 inhibition can improve the standard anticancer treatment efficacy. Acting on the MMP-9 pathway, NF- κ B mediated signaling can be initiated for tumor suppression [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, ubiquitin-proteasome inhibitors of any step inhibit NFκB activation by stabilizing IκB [27]. IKK protein is phosphorylated at two serine residues (Ser176/180 of IKKα or Ser 177/181 of IKKβ) and subsequently induces the phosphorylation of IκBα at Ser 32/36 [28]. Significantly inhibiting the phosphorylation of p-IKKα (Ser176/180) and p-IκBα (Ser32) then leads to a decrease in nuclear levels of NFκB p65 [28].…”
Section: Discussionmentioning
confidence: 99%
“…IKK protein is phosphorylated at two serine residues (Ser176/180 of IKKα or Ser 177/181 of IKKβ) and subsequently induces the phosphorylation of IκBα at Ser 32/36 [28]. Significantly inhibiting the phosphorylation of p-IKKα (Ser176/180) and p-IκBα (Ser32) then leads to a decrease in nuclear levels of NFκB p65 [28]. Various anticancer drugs have shown anti-NFκB activity, which may be related to their anti-tumor effects, possibly by reducing NFκBs proliferative and antiapoptotic activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that exendin-4 inhibits NF-κB activation in ovarian and breast cancer cells, thus inducing cell death and suppression of migration and invasion. 19,24 As a downstream cytokine of NF-κB signaling, SDF-1 and its receptor CXCR4 play an important role in pancreatic cancer progression. Our previous study showed that SDF-1 is predominantly expressed in PSCs, and its upregulation in PSCs increases the invasion of pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that exendin-4 inhibits NF-κB activation in several cancer cells, 19,24 we measured the levels of p65 and phospho-p65 (p-p65) in PSCs with or without exendin-4 treatment. As shown in Figure 2A and B, exendin-4 suppressed the expression of p-p65 and p-IκBα and enhanced that of IκBα.…”
Section: Exendin-4 Attenuated Nf-κb-mediated Sdf-1 Secretionmentioning
confidence: 99%